Enzymatic bionanocatalysts for combating peri-implant biofilm infections by specific heat-amplified chemodynamic therapy and innate immunomodulation. (March 2023) - Su, Zheng; Kong, Lingtong; Mei, Jiawei; Li, Qianming; Qian, Zhengzheng; Ma, Yuanyuan; Chen, Yue; Ju, Shenghong; Wang, Jiaxing; Jia, Weitao; Zhu, Chen; Fan, Wenpei
Abstract: Bacterial biofilm-associated infection is a life-threatening emergency contributing from drug resistance and immune escape. Herein, a novel non-antibiotic strategy based on the synergy of bionanocatalysts-driven heat-amplified chemodynamic therapy (CDT) and innate immunomodulation is proposed for specific biofilm elimination by the smart design of a biofilm microenvironment (BME)-responsive double-layered metal-organic framework (MOF) bionanocatalysts (MACG) composed of MIL-100 and CuBTC. Once reaching the acidic BME, the acidity-triggered degradation of CuBTC allows the sequential release of glucose oxidase (GOx) and an activable photothermal agent, 2, 2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). GOx converts glucose into H2 O2 and gluconic acid, which can further acidify the BME to accelerate the CuBTC degradation and GOx/ABTS release. The in vitro and in vivo results show that horseradish peroxidase (HRP)-mimicking MIL-100 in the presence of self-supplied H2 O2 can catalyze the oxidation of ABTS into oxABTS to yield a photothermal effect that breaks the biofilm structure via eDNA damage. Simultaneously, the Cu ion released from the degraded CuBTC can deplete glutathione and catalyze the splitting of H2 O2 into OH, which can effectively penetrate the heat-induced loose biofilms and kill sessile bacteria (up to 98.64%), such as E. coli and MRSA. Particularly, MACG-stimulated M1-macrophage polarization suppresses the biofilm regeneration by secreting pro-inflammatory cytokines ( e.g., IL-6, TNF-α, etc. ) and forming a continuous pro-inflammatory microenvironment in peri-implant biofilm infection animals for at least 14 days. Such BME-responsive strategy has the promise to precisely eliminate refractory peri-implant biofilm infections with extremely few adverse effects.